SOFTWARE AND METHODOLOGICAL SUPPORT FOR DEVELOPING AUTOMATION-RELATED PROFESSIONAL COMPETENCIES OF FUTURE ELECTRICAL ENGINEERS: https://doi.org/10.5281/zenodo.20390271 - Akhmedov , Abdurauf (Scientific practical conference, 2026)
This thesis discusses the software and methodological support for developing automation-related professional competencies of future electrical engineers. The study analyzes the pedagogical possibilities of using modern digital technologies in teaching the course “Electric Machines” including PLC programming, TIA Portal, MATLAB Simulink, SCADA systems, and virtual laboratories. The paper also considers the formation of students’ practical skills through modeling and automated control of electric machines. Based on a competency-oriented approach, the integration of interactive teaching methods and software tools is substantiated as an effective means of improving the professional training of electrical engineering students. The obtained results are important for enhancing the teaching methodology of the “Electric Machines” course in higher educational institutions through modern educational technologies.